The effects of informal settlement upgrading programme on service delivery in Disteneng, Polokwane City - Ngoepe, Malesela Rejoyce (My University, 2017)
Informal settlements are known as areas that are established illegally and have the poorest access to basic services. ISU programme addresses the challenges related to illegal land occupancy and other poor living conditions in informal areas. Such settlements are associated with service provision distress around the world. Evidently, the increasing service delivery protest shows the inadequacy in access, availability and quality of basic amenities. Furthermore, the urban renewal programme intervenes to remedy severe circumstances that include environmental disruptions that threaten lives and forceful evictions. Moreover, proliferation of houses has a negative impact on the provision of infrastructure improvement. Informal settlements are usually characterised by exceedingly poor access to basic services. The poor occupy more centrally located pieces of land left over because they were not suitable for housing. As a result, vulnerable households experience harsh environmental conditions. Nevertheless, social conditions of informal settlements are noticeable and usually used to describe informal dwellings. The ISU programme plays number of roles in addressing poor living conditions. There are rationale and institutions that plays both major and minor roles in maximising the outcomes of the upgrading programme. The success of ISU programme may not be noticeable in other informal settlements because of different circumstances. The effects of ISU programme on service delivery have not being studied in Disteneng. Therefore, the study investigates the effects of the programme on service delivery in Disteneng to test different arguments revealed on both international and South African contexts. It is against this background that the study argues that the effects of ISU programme on service delivery in informal settlements are not automated but subject to circumstance. Moreover, the formative evaluation research used both qualitative and quantitative to provide their opinions on the conditions of a typical informal area, the roles and the rational status of service delivery and the effects of the ISU programme. In addition, the Qualitative method gives the reader an in-depth understating of ISU programme and service delivery. Disteneng is used as a study area to test the argument on the effects of the upgrading programme on service delivery. A non-probability sampling design was used in order to access household easily. Moreover, the study utilized the convenience sampling method. Literature survey was conducted through the use of books, government documents, journal articles and conference papers. The study used questionnaires and interview schedule to collect factual data. Data collected through journal articles, government documents, conference papers, questionnaires, interview and observation on the effects on ISU programme on service delivery, the study revealed that theoretically, the ISU programmes has positively affected service provision in informal settlements. The thesis also established that there is a combination of success stories and failures in the context of South Africa. Lastly, ISU programme has positively affected service provision in the Disteneng. However, households in the area are not satisfied with most of the services provided. The study recommended adequate investment in basic service to ensure that household services such as water, sanitation and electricity could be provided in Disteneng. Furthermore, to improve social circumstances such as crime, a mobile police station should be put in place. The thesis concludes that the ISU programme have a positive effect on service delivery in Disteneng. The conclusion is influenced by the improvements that are now seen in the area. Those developments include legalization of the settlement, secure tenure and access to water and sanitation in the area
Thesis (M. Dev. (Planning and Management)) -- University of Limpopo, 2017
Keywords: Informal settlement; Service delivery; Upgrading programme; Community development -- South Africa; Basic needs -- Developing countries; Rural development; Municipal services -- South Africa -- Limpopo